The sensory act as the object of the representation of a feeling (Research, Society and Development, 2021)
The scientific study of the sensory act aims to make a distinction between the relation of sensations with the Series of Feelings, permanently present in consciousness, and the relation of sensations with the groups of Permanent Possibilities of Sensation, which intervene intermittently in consciousness. However, we started from the description of these two concepts, specific to scientific psychology and attributed to the psychological theory of William Hamilton (1853; 1859; 1860), until considering the critical gaze of John Stuart Mill (1869). From there, we sought to analyze our object of study, which is the sensory act, and this according to this second relationship phenomenon in order to contribute to scientific studies from two perspectives, which are: a) behavior, because according to the causal relations of David Hume (1739), as for the theory of causality being the initial theoretical basis to support the study of our object, behavior is the effect of sensory acts, which are the cause of it and making the behavior happen through the actions of thinking or acting otherwise; b) the memory of immediately past psychic phenomenal, because according to the scientific description of the representation of feeling, which is the second theoretical basis of our study framed by Franz Brentano (2008), feeling has an object. The results will be the product of observations on the effects of the sensory act. The conclusions of the study will concern the relevance of the conditions under which these possibilities are realized in consciousness.